New ideas in optimization - Corne, David; Dorigo, Marco; Glover, Fred (Advanced topics in computer science series, 1999)
Optimization is a pivotal aspect of software design. The techniques treated in this text represent research as elucidated by the leaders in the field. The optimization methods are applied to real problems, such as hilllclimbing, simulated annealing, and tabu search.